On the uniqueness of an element of the best $L_1$-approximation for functions with values in a banach space - Babenko, V. F.; Gorbenko, M. E.; Бабенко, В. Ф.; Горбенко, М. Е.; Бабенко, В. Ф.; Горбенко, М. Е. (Institute of Mathematics, NAS of Ukraine, 2000)
We study the problem of uniqueness of an element of the best $L_1$-approximation for continuous functions with values in a Banach space. We prove two theorems that characterize the uniqueness subspaces in terms of certain sets of test functions.